Legal Protection Of Children With Special Needs In The Era Covid-19 According To Islamic law Perspective - Mhd Yadi Harahap; Hafsah; Mashuri Siregar Hall; M. Fajri Syahroni Siregar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The Indonesian Ulema Council has issued a fatwa, one of which is a fatwa on the Ahmadiyya group to safeguard the orthodoxy of Sunni theology from deviant theology. This study aims to examine the MUI fatwa on Ahmadiyah from the perspective of Islamic law and human rights using the theory of religious freedom developed by Tore Lindholm. This normative juridical research uses a conceptual and historical approach. The primary data source is the Fatwa Compilation of the Indonesian Ulama Council Since 1975, books of interpretation, hadith, and fiqh. Data collection techniques using documentation and interviews. Interviews were conducted with informants from the Indonesian Ulema Council (MUI). The results showed that the MUI Fatwa regarding the Ahmadiyah group was based on two arguments. The first argument is that Islamic law is based on the Qur'an, hadith, and ijma' according to the interpretation of classical scholars. The second argument is the limitation of human rights because the Ahmadiyya group can pose a threat to public order. MUI considers that any group or theology that is declared